Nurturing Independent Character: The Vital Role of Grade 1 Teachers: Mengungkap Peran Penting Guru dalam Membangun Karakter Mandiri pada Siswa Kelas 1: Studi Fenomenologi Kualitatif - Istyo Indah Kurniasari; Machful Indra Kurniawan (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the role of teachers during the learning process to form the independent character of Grade 1 students at SDN Pejangkungan Prambon. This study uses a qualitative approach phenomenology, where the background in the phenomenon or the fact that in Grade 1 SDN Pejangkungan Prambon there are students who experience problems related to independent character. In every learning process there are still many students who have not been able to do it themselves and still rely on teachers. Therefore, researchers want to examine whether there is a role of teachers during the learning process to form the independent character of students. For this study using trisngulasi technique is taken from observation data, interviews and documentation of teachers in Grade 1 SDN Pejangkungan. And from the results of research that researchers get that teachers play a good role as educators, teachers, and mentors in forming independent character student. Highlights: Teachers as Role Models: The study highlights the vital role of teachers in serving as positive role models for Grade 1 students, influencing their development of independent character. Fostering Autonomy: The research emphasizes the importance of the learning process in nurturing students' autonomy and self-reliance, with teachers playing a significant role in guiding and empowering them. Triangulation Approach: By utilizing triangulation techniques through observation data, interviews, and documentation, the study provides a comprehensive understanding of how teachers contribute to the formation of independent character in Grade 1 students at SDN Pejangkungan. Keywords: Teachers, Independent Character, Grade 1 Students, Learning Process, SDN Pejangkungan